2000
DOI: 10.1046/j.1365-2168.2000.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after restorative panproctocolectomy for ulcerative colitis decreases an otherwise enhanced quality of life

Abstract: Poor function after pelvic pouch surgery offsets any advantage in body image over an ileostomy. Thus, overall quality of life and perceived monetary damage were the same for the two operations. Improved pelvic pouch function is likely to be reflected in better quality of life after restorative panproctocolectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 18 publications
0
19
1
Order By: Relevance
“…16 Patients with IPAA, continent ileostomy, or ileostomy have been shown to score similarly with regard to HRQL. 30 Furthermore, two studies have demonstrated that the HRQL of patients with ileostomy or urostomy does not differ from that of the general population. 31,32 Our results may not be fully comparable with those of the above studies because patients with a failing pouch could be special with regard to HRQL and thus not comparable with patients with ileostomies in general.…”
Section: Discussionmentioning
confidence: 99%
“…16 Patients with IPAA, continent ileostomy, or ileostomy have been shown to score similarly with regard to HRQL. 30 Furthermore, two studies have demonstrated that the HRQL of patients with ileostomy or urostomy does not differ from that of the general population. 31,32 Our results may not be fully comparable with those of the above studies because patients with a failing pouch could be special with regard to HRQL and thus not comparable with patients with ileostomies in general.…”
Section: Discussionmentioning
confidence: 99%
“…Impediments associated with elimination and specific public restrooms were also reported in persons with continent ileostomy. 18 Problems with odor, gas, noise and leakage were found in a study by O'Bichere et al, 22 which showed that altered bowel emptying affected QoL in persons with an IPAA, who showed significantly worse scores in regard to altered bowel emptying compared with those who had an ileostomy or a continent ileostomy. The disease-specific adjustment questionnaire used in our study addresses the issue of worries about producing embarrassing odors in the bathroom but does not include questions regarding noise and gas.…”
Section: Discussionmentioning
confidence: 99%
“…Among 5 studies published during the past decade that compared TPC and IPAA subjects, 4 reported that the QOL after IPAA and TPC is the same. [5][6][7][8][9] As such, restoration of normal QOL may be related primarily to the cure of disease-related symptoms, and preservation of the anus may actually have little added effect. 7 In short, it has been remarkably difficult to demonstrate an additional QOL benefit for IPAA after total proctocolectomy in an objective manner.…”
mentioning
confidence: 99%